Analysis of apical hook formation in Alaska pea with a 3-D clinostat and agravitropic mutant ageotropum - Miyamoto, Kensuke; Yamasaki, Takahiro; Uheda, Eiji; Ueda, Junichi (Frontiers in Plant Science, 2014)
The formation of the apical hook in dicotyledonous seedlings is believed to be effected by gravity in the dark. However, this notion is mostly based on experiments with the hook formed on the hypocotyl, and no detailed studies are available with the developmental manners of the hook, particularly of the epicotyl hook. The present study aims at clarifying the dynamics of hook formation including the possible involvement of gravity. Time-course studies with normal Alaska pea (Pisum sativum L., cv. Alaska) and an agravitropic pea mutant, ageotropum, under the 1-g conditions and on a 3-D clinostat revealed that 1) the apical hook of the epicotyl forms by the development of the arc-shaped plumule of the embryo existing in the non-germinated seed. The process of formation consists of two stages: development and partial opening, which are controlled by some intrinsic property of the plumule, but not gravity. Approximately when the epicotyl emerges from the seed coat, the hook is established in both pea varieties. In Alaska the established hook is sustained or enhanced by gravity, resulting in a delay of hook opening compared with on a clinostat, which might give an incorrect idea that gravity causes hook formation. 2) During the hook development and opening processes the original plumular arc holds its orientation unchanged to be an established hook, which, therefore, is at the same side of the epicotyl axis as the cotyledons. This is true for both Alaska and ageotropum under 1-g conditions as well as on the clinostat, supporting finding (1). 3) Application of auxin polar transport inhibitors, hydroxyfluorenecarboxylic acid, naphthylphthalamic acid, and triiodobenzoic acid, suppressed the curvature of hook by equal extents in Alaska as well as ageotropum, suggesting that the hook development involves auxin polar transport probably asymmetrically distributed across the plumular axis by some intrinsic property of the plumule not directly related with gravity action.